HEAVY METAL CONCENTRATIONS IN SHALLOW MARINE SEDIMENTS AFFECTED BY SUBMARINE TAILINGS DISPOSAL AND ARTISANAL GOLD MINING, BUYAT-RATOTOTOK DISTRICT, NORTH SULAWESI, INDONESIA - Edinger E.N.; Siregar P.R.; Blackwood G.M. (My University, 2007)
Trace element concentrations in shallow marine sediments of the Buyat-Ratototok district of North Sulawesi, Indonesia, are affected by submarine disposal of industrial gold mine tailings and unregulated dumping of tailings and wastewater from small-scale gold mining using mercury amalgamation. Industrial mine tailings contained 590–690 ppm arsenic, 490–580 ppm antimony, and 0.8–5.8 ppm mercury. Tailings-affected sediment As and Sb concentrations were 20–30 times higher than in muddy sediments not contaminated with tailings, and 50–60 times higher than pre-mining average. Highest mercury concentrations were observed in sediments affected by small-scale mining using mercury amalgamation (5–29 ppm). Concentrations of most other trace elements were comparable in sediments affected by both types of mining and were slightly higher than regional averages for sediments collected before the onset of industrial mining. Elevated concentrations of both As and Sb in approximately equal proportions suggest tailings dispersal of at least 3.5 km. Mercury released from artisanal gold mining dispersed up to 4 km from river mouths. Slight increases in concentrations of non-mercury trace elements in areas affected by artisanal mining over pre-industrial mining concentrations were probably caused by increased rates of erosion.
Keywords: MINE TAILINGS; COASTAL CONTAMINATION; HEAVY METALS